2020
DOI: 10.35542/osf.io/h746s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Instructor strategies to alleviate student stress and anxiety in colleges and universities

Abstract: While student stress and anxiety are frequently cited as having negative effects on students’ academic performance, the role that instructors can play in mitigating these issues is often underappreciated. We provide summaries of different evidence-based strategies that instructors can employ to address and ameliorate student stress and anxiety that range from changes in instructional strategies to specific classroom interventions. We begin by highlighting ways in which instructors can learn about and prepare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 109 publications
(136 reference statements)
2
2
0
Order By: Relevance
“…Second, student responses highlight the need for instructors to take deliberate steps to promote engagement among students; allowing the same breakout groups each time and providing time for community building may be beneficial. Third, instructors should be aware of the many challenges that students are facing when learning remotely, including a decrease in motivation and increases in stress and anxiety, 2,3,18 and can take steps to encourage intrinsic motivation of students and reduce student stress 31,37 . We also find that students appreciated having highly structured courses, in line with past reports that more structured courses promote greater learning 38,39 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, student responses highlight the need for instructors to take deliberate steps to promote engagement among students; allowing the same breakout groups each time and providing time for community building may be beneficial. Third, instructors should be aware of the many challenges that students are facing when learning remotely, including a decrease in motivation and increases in stress and anxiety, 2,3,18 and can take steps to encourage intrinsic motivation of students and reduce student stress 31,37 . We also find that students appreciated having highly structured courses, in line with past reports that more structured courses promote greater learning 38,39 .…”
Section: Discussionsupporting
confidence: 82%
“…Third, instructors should be aware of the many challenges that students are facing when learning remotely, including a decrease in motivation and increases in stress and anxiety, 2,3,18 and can take steps to encourage intrinsic motivation of students and reduce student stress. 31,37 We also find that students appreciated having highly structured courses, in line with past reports that more structured courses promote greater learning. 38,39 Students reported that having regular formative assessments, such as problem sets and discussion questions, as well as having supplemental instruction led by undergraduates who had previously taken the course, were highly beneficial to their learning, and instructors can promote additional structure in their courses and add in frequent, low-stakes formative assessments and practice resources for students.…”
Section: Implications For Biology and Biochemistry Instructorssupporting
confidence: 87%
“…Any changes that we make to our curriculum and courses should always be made with student learning in mind, and steps that prevent or deter cheating but damage student learning are counterproductive. In addition, given the increases in student stress and anxiety during the pandemic, instructors should couple these approaches with evidence-based strategies to reduce student stress and anxiety ( 70 ). I hope that this guide provides useful insight into promoting academic integrity in online biology courses during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Instructors should also be aware that such online proctoring may lead to increases in student anxiety and lowered student performance ( 68 , 69 ), and the use of such software may raise concerns about privacy and security. As such, if instructors do use such software, it may be helpful to explain the workflow in advance, provide practice runs with the software, allow for alternatives for students who may not be able to successfully use this software, and take steps to decrease student stress and anxiety ( 70 ).…”
Section: What Strategies Can Biology Instructors Take To Uphold Academentioning
confidence: 99%